UDDER TEAT MORPHOLOGY AND BODY MEASUREMENTS AND THEIR RELATIONSHIP WITH MILK YIELD AND MILKING TRAITS IN GIR COWS - SINGHAI, S.K; RAVIKALA, K; MURTHY, K S; GAJBHIYE, P.U; VATALIYA, P.H; SAVSANI, H.H. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTAn investigation was undertaken to study the udder, teat and body measurements asaffected by parity and their relationship with milk yield and milking traits in 100 Gir cows atCattle Breeding Farm, JAU, Junagadh. Mean udder length, width and depth were found to be(cm) 45.99 ± 2.07, 20.51 ± 0.99 and 20.29 ± 1.04, respectively and were significantly (P < 0.01)affected according to different orders of lactations. Positive and significant correlations wereobserved among all the udder measurements. However, the correlation was significant amongUdder length, Udder width and daily milk yield (kg) (P